2015
DOI: 10.1111/jch.12572
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Peripheral and Central Blood Pressure in Patients With Sickle Cell Disease

Abstract: Blood pressure (BP) in patients with sickle cell disease (SCD) has been reported to be lower than in persons in the general population. Data on arterial stiffness, which is an important risk factor for the progression of BP, are inconclusive for this patient population. Forty‐five adult patients with SCD and 40 controls matched for sex, age, and body mass index were studied. Brachial systolic BP (SBP) and diastolic BP (DBP) were significantly lower in the patient group (SBP 115.1±13.8 mm Hg vs 121.9±11.3 mm Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(56 reference statements)
2
12
0
1
Order By: Relevance
“…This may be due to loss of sodium and water related to medullary tonicity defects (25). In addition to, high levels prostaglandin, decrease vascular reactivity and systemic vaso-dilatation response to micro-vascular dysfunction(6) or might be due to chronic activation of Nitric Oxide system (NO) (15,25).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to loss of sodium and water related to medullary tonicity defects (25). In addition to, high levels prostaglandin, decrease vascular reactivity and systemic vaso-dilatation response to micro-vascular dysfunction(6) or might be due to chronic activation of Nitric Oxide system (NO) (15,25).…”
Section: Discussionmentioning
confidence: 99%
“…They studied arterial stiffness and augmentation index (AIx) in patients with sickle cell disease (SCD). In their study, AIx was significantly higher in SCD patients compared with healthy controls; however, pulse wave velocity (PWV) was comparable between two groups, 1 suggesting the existence of different determinants of AIx and PWV. Patients with type 2 diabetes have increased arterial stiffness.…”
mentioning
confidence: 84%
“…8,9 Evidence on the prevalence of hypertension and subclinical vascular damage as assessed by arterial stiffness in SCD populations is relatively few and with inconsistent results. [9][10][11][12] Some studies showed low blood pressure (BP) levels in SCD patients and similar levels of pulse wave velocity (PWV) with healthy controls, 10 while others showed increased stiffness and an inverse association of PWV with BP. 9,11 The interaction of BP and arterial stiffness on the in the study 16 pediatric SCD (HbS/β-thalassemia, S/β-thal) patients and 16 consecutive children at risk for hypertension referred to our hypertension clinic that served as high-risk controls.…”
Section: Introductionmentioning
confidence: 99%